Tunable emission color and anti-thermal-quenching behaviors in niobates for high-sensitive optical thermometry. (March 2023) - Zhao, Bin; Chen, Yuqi; Xue, Yu; Mao, Qinan; Bai, Gongxun; Liu, Meijiao; Zhong, Jiasong
Graphical abstract: Highlights: The tunable multi-color emission is realized via the energy transfer from Bi 3+ to Eu 3+ ions. An anti-thermal-quenching behavior of Eu 3+ ion and a great emission loss of Bi 3+ ion can be achieved. The maximum Sa and Sr reach as high as 0.318 K −1 and 1.62%K −1 . The surrounding temperature can be qualitatively estimated by observing the thermochromic behaviors. The designed phosphor presents a multiplicity of applications in non-contact temperature measurement and white LED. Abstract: Non-contact remote optical thermometers as a significant technique have been extensively developed. However, it is still a challenge to design new Bismuth-doped phosphor materials with tunable spectra for high-sensitive optical temperature sensors. Herein, a novel Yx Lu1-x NbO4 :Bi 3+ (0 ≤ x ≤ 1.0) phosphor is constructed by the isomorphic end components LuNbO4 and YNbO4 . Owing to the modification of crystal field strength around Bi 3+ ions, the emission positions controllably shifted from 475 to 462 nm with the increase of Y 3+ ions concentrations. Besides, systematic luminescence modifying from blue to red across the white light region could be achieved via the design of Bi 3+ →Eu 3+ energy transfer (ET). Intriguingly, an anti-thermal-quenching behavior of Eu 3+ ion originating from the ET is found in Y0.8 Lu0.2 NbO4 :Bi 3+, Eu 3+ (YLNO:Bi 3+, Eu 3+ ) phosphors, while Bi 3+ ion presents a great emission intensity loss with only retaining 46.8% at 383 K. Based on the disparate thermal responses, the fluorescence intensity ratio (FIR) of Eu 3+ to Bi 3+ demonstrates excellent thermometry properties from 303 to 503 K. The maximum absolute sensitivity ( Sa ) and relative sensitivity ( Sr ) reach 0.318 K −1 (@328 K) and 1.62%K −1 (@393 K). In addition, the thermochromic performance of the resultant phosphors could be applied to qualitatively estimate the surrounding temperature. The spectral adjustability and high-sensitive of the developed phosphors highlight their multiplicity of applications in non-contact temperature measurement and white LED.